Is Organic Rice bean (Vigna umbellata) Farmers Economically better Off? An Empirical Analysis - Chiphang, Singyala; Singh, Ram; Feroze, S. M. (Indian Journal of Extension Education, 2021)
The study was conducted in North Eastern Hill (NEH) region of India during 2018-2020. Multistage sampling technique was adopted. Sikkim was selected purposively as the control state and Nagaland was selected based on the highest area and production under pulses. 60 respondents each from organic adopter and non-adopter were selected making a total sample size of 120. The growth rate in area, production and productivity at the world, India and NEH states were found to be positive. However, higher growth rate were observed for the NEH region. Significance difference was observed only on cost of fertilizers. The total cost of rice bean cultivation was lower in organic adopter by 1.71 per cent. The average yield was significantly higher for the organic adopter. The gross income and net income were also higher for the organic adopter. Organic farming was found to be more profitable and it can enhance the farmer’s income. Allocative efficiency indicates that all the resources used in the region need to be increase so as to achieve the maximum potential yield and henceforth increase the returns.
Keywords: Allocative efficiency; Gross income; Net income; Organic; Pulses; Rice bean